1991
DOI: 10.1021/bi00107a022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a major brain tubulin variant which cannot be tyrosinated

Abstract: Brain tubulin preparations contain an abundant type of tubulin which does not undergo the normal cycle of tyrosination-detyrosination, and whose nature is still unknown. We have used peptide sequence analysis and mass spectrometry combined with immunological procedures to show that this non-tyrosinatable tubulin has a specific primary structure. It differs from the tyrosinated isotype in that it lacks a carboxy-terminal glutamyl-tyrosine group on its alpha-subunit. Thus, non-tyrosinatable tubulin originates fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
138
1
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(146 citation statements)
references
References 41 publications
1
138
1
3
Order By: Relevance
“…Two other unique post-translational modifications involve the presence of a polyglutamyl-or polyglycyl side chain attached via an isopeptide bond to a particular glutamic acid residue in the carboxyterminal region of ct-and 13-tubulin. The exact position of this modified residue has been identified in all brain tubulins [3,8,[10][11][12][13]. The more recently discovered polyglycylation has been documented for ct-and 13-tubulin from the ciliary axonemal microtubules of the protist Paramecium [14] and from the sperm axonemal microtubules of mammals [15] (Plessmann, U. and Weber, K. unpublished results) and sea urchins [16].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other unique post-translational modifications involve the presence of a polyglutamyl-or polyglycyl side chain attached via an isopeptide bond to a particular glutamic acid residue in the carboxyterminal region of ct-and 13-tubulin. The exact position of this modified residue has been identified in all brain tubulins [3,8,[10][11][12][13]. The more recently discovered polyglycylation has been documented for ct-and 13-tubulin from the ciliary axonemal microtubules of the protist Paramecium [14] and from the sperm axonemal microtubules of mammals [15] (Plessmann, U. and Weber, K. unpublished results) and sea urchins [16].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Thus the carboxyterminal tyrosine of certain ct-tubulins is subject to a detyrosination/tyrosination cycle based on a carboxypeptidase and the well-characterized tubulin-tyrosine ligase [5,6]. After loss of the tyrosine and penultimate glutamic acid residue the resulting tubulin is no longer a substrate for tubulintyrosine ligase [7][8][9]. Two other unique post-translational modifications involve the presence of a polyglutamyl-or polyglycyl side chain attached via an isopeptide bond to a particular glutamic acid residue in the carboxyterminal region of ct-and 13-tubulin.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…16,18,28 The PVDF membranes spotted with equal amount (1 g) of synthetic peptides corresponding to COOH terminal 7 amino acid residues of Tyr-tubulin (CEEE-GEEY), Glu-tubulin (CGEEEGEE) and ⌬2-tubulin (CEGEEEGE) were immunoblotted with rabbit anti-Tyr-tubulin antibody (Fig. 3a, top), anti-Glu-tubulin antibody (Fig.…”
Section: Specific Antibodies and Catalytic Activity Of Httlmentioning
confidence: 99%
“…14 Recently, rat TTL cDNA has also been isolated. 15 Interestingly, in 1991, Paturle-Lafanechere et al 16 identified a nontyrosinatable variant of tubulin that lacked 2 amino acid residues, glutamic acid and tyrosine, at the COOH terminus (⌬2-tubulin). ⌬2-tubulin was found to accumulate in mature neurons and in stable microtubule assemblies in cells.…”
mentioning
confidence: 99%
“…The deTyr-tubulin can be converted back to Tyr-tubulin through the addition of Tyr by the enzyme tubulin tyrosine ligase (TTL) (22). Alternatively, the deTyr-tubulin can be converted to delta2-tubulin by the removal of C-terminal Glu (18,23). Another post-translational modification of ␣-tubulin as well as ␤-tubulin involves the addition and removal of polyglutamyl (polyE) side chains (18,24).…”
mentioning
confidence: 99%